P 2 Effects of deep brain stimulation (DBS) in the entopeduncular nucleus (EPN) in dystonic dtsz hamsters. (May 2022) - Lüttig, A.; Perl, S.; Paap, M.; Franz, D.; Heerdegen, M.; Köhling, R.; Richter, A.
Abstract : Introduction: DBS of the globus pallidus internus (GPi; entopeduncular nucleus, EPN, in rodents) has become important for the treatment of generalized dystonia. There is evidence that striatal dysfunctions cause a disturbed thalamocortical inhibition via altered neuronal activity in the GPi/EPN. However, the pathophysiology as well as the mechanisms of DBS are largely unknown, which hampers the detection of drug targets. In our project of the CRC "Electrically active implants" we aim to elucidate mechanisms of DBS in animal models of dystonia. We recently found that short-term (3 h) EPN-DBS with 130 Hz (50 µA, 60 µs) improves paroxysmal dystonia in the dt sz mutant hamster 1 and reduces spontaneous excitatory cortico-striatal activity in brain slices of this model 2, indicating fast effects in synaptic plasticity. In the present study, we therefore examined whether short-term DBS leads to changes of c-Fos, an immunohistochemical marker of neuronal activity, in EPN-related network regions. Materials & Methods: For immunohistochemistry we used brains of stimulated dt s z hamsters, in which DBS had improved dystonia, as well as sham-stimulated and naïve animals and performed cell counting and fluorescence intensity measurements of c-Fos within the basal ganglia network. In addition, we performed double labeling of c-Fos with GAD67 and with parvalbumin (PV), respectively, in brain slices of the same animals. Results: After DBS vs. sham, c-Fos + around the electrode was increased. Unexpectedly, c-Fos + cells were decreased in deep cerebellar nuclei (DCN) after DBS, but no changes became evident within the whole EPN, habenula, ventromedial thalamus, cortex and striatum. Cell counting of c-Fos activated GAD67 + as well as activated PV + cells showed no differences between the groups in motor cortex and striatum. Conclusion: With regard to recent electrophysiological data, we expected c-Fos changes especially in cortical GABAergic neurons after DBS in dt sz hamsters. The lack of changes within the basal ganglia network could be related to the short duration of stimulation or the time interval between stimulation and c-Fos staining. Ongoing long-term EPN stimulations, now feasible by a new fully implantable stimulator 3, probably lead to more pronounced effects within the network and will be useful to verify the DCN effects. Funded by the DFG within the Collaborative Research Centre 1270 ELAINE. References 1. Paap M et al. (2020) Deep brain stimulations in a phenotypic model of dystonia: effects of different frequencies by using an optimized stimulator. Neurobiol Dis. 147, 105163. 2. Heerdegen M et al. (2021) Mechanisms of pallidal deep brain stimulation: alteration of cortico-striatal synaptic communication in a dystonia animal model. Neurobiol Dis. 154, 105341. 3. Plocksties F et al. (2021) The software defined implantable modular platform (STELLA) for preclinical deep brain stimulation research in rodents. J. Neural Eng. 18, 056032.